Does lumbar spinal stenosis increase the risk of spondylotic cervical spinal cord compression? - Adamova, Blanka; Bednarik, Josef; Andrasinova, Tereza; Kovalova, Ivana; Kopacik, Roman; Jabornik, Michal; Kerkovsky, Milos; Jakubcova, Barbora; Jarkovsky, Jiri (European spine journal, 2015)
PURPOSE: The aim of this prospective cross-sectional observational comparative study was to determine the prevalence of spondylotic cervical cord compression (SCCC) and symptomatic cervical spondylotic myelopathy (CSM) in patients with symptomatic lumbar spinal stenosis (LSS) in comparison with a general population sample and to seek to identify predictors for the development of CSM. METHODS: A group of 78 patients with LSS (48 men, median age 66 years) was compared with a randomly selected age- and sex-matched group of 78 volunteers (38 men, median age 66 years). We evaluated magnetic resonance imaging findings from the cervical spine and neurological examination. RESULTS: The presence of SCCC was demonstrated in 84.6% of patients with LSS, but also in 57.7% of a sample of volunteers randomly recruited from the general population. Clinically symptomatic CSM was found in 16.7% of LSS patients in comparison with 1.3% of volunteers (p = 0.001). Multivariable logistic regression proposed the Oswestry Disability Index of 43% or more as the only independent predictor of symptomatic CSM in LSS patients (OR 9.41, p = 0.008). CONCLUSIONS: The presence of symptomatic LSS increases the risk of SCCC; the prevalence of SCCC is higher in patients with symptomatic LSS in comparison with the general population, with an evident predominance of more serious types of MRI-detected compression and a clinically symptomatic form (CSM). Symptomatic CSM is more likely in LSS patients with higher disability as assessed by the Oswestry Disability Index.
Keywords: lidé; magnetická rezonanční tomografie; Adult; Middle Aged; Lumbar spinal stenosis; Case-Control Studies; Cervical stenosis; Tandem stenosis; prospektivní studie; komprese míchy; Magnetic Resonance Imaging; Female; posuzování pracovní neschopnosti; spinální stenóza; Humans; průřezové studie; Disability Evaluation; bederní obratle; studie případů a kontrol; Cross-Sectional Studies; neurologické vyšetření; Prospective Studies; Neurologic Examination; lidé středního věku; Lumbar Vertebrae; Spinal Cord Compression; spondylóza; mužské pohlaví; Cervical cord compression; ženské pohlaví; Aged, 80 and over; senioři nad 80 let; Male; Aged; Cervical myelopathy; Spinal Stenosis; dospělí; Spondylosis; senioři